In vitro effect of gut microbiota-derived indole-3-propionic acid on insulin resistance - Franco, IS (2024)
"BACKGROUND AND AIMS: Although indole-3-propionic acid (IPA) has been shown to exhibit preventive effects against type 2 diabetes (T2D), nothing is known regarding its ability to restore T2D-associated hallmarks. As such, this study aimed to assess the ability of IPA to reverse the metabolic phenotype of insulin-resistant 3T3-L1 adipocytes.(...)"